Effect of persimmon leaves (Diospyros kaki) on goblet cell density and inflammation in experimental dry eye model - Kim, Kyung-A; Lee, Chung Hyun; Kang, Tae Kyeom; Yang, Sung Jae; Lee, Chang Yong; Lee, Wook-Bin; Jung, Sang Hoon (한국응용생명화학회, 2020)
The efficacy of ethanol extract ofDiospyros kaki(EEDK) on dry eye (DE) was determined using an experimental mouse model. Experimental groups included three treated with various amounts of EEDK and one treated with omega-3 for 2 weeks. Damage to the ocular surface was evaluated, and the presence of conjunctival goblet cells was determined. Moreover, the inflammatory response was analyzed via RT-PCR analysis and a reporter gene assay. Fluorescein staining intensity decreased in the EEDK treatment group, and goblet cell density increased significantly in a dose-dependent manner. Pro-inflammatory cytokines were upregulated in human corneal epithelial cells treated with Pam3Cys-Ser-(Lys)-4. However, pro-inflammatory cytokines were downregulated at the mRNA level upon treatment with EEDK. Furthermore, EEDK regulated Pam3CSK4-induced gene expression through interferon regulatory factors. EEDK effectively improves the conjunctival goblet cell density and reduces the inflammatory response by reducing interferon regulatory factor activation downstream of Toll-like receptors in DE. Therefore, EEDK could be beneficial agents for preventing and treating DE.